2010
DOI: 10.1111/j.1540-8167.2009.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Anterior Line: An Alternative Linear Lesion in Perimitral Flutter

Abstract: The MAL is a safe and effective linear lesion for the treatment of perimitral LAF. Its value compared to more established linear lesions as the mitral isthmus line has to be evaluated in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 27 publications
1
53
0
1
Order By: Relevance
“…Routine isolation of the posterior wall does not seem to achieve better results in a prospective randomized study [227]. On the other hand, it has been widely demonstrated that incomplete block across the ablation lines can be responsible for AT recurrence [228][229][230]. Therefore, if additional linear lesions are applied, line completeness should be demonstrated by mapping or pacing maneuvers.…”
Section: Linear Ablationmentioning
confidence: 93%
“…Routine isolation of the posterior wall does not seem to achieve better results in a prospective randomized study [227]. On the other hand, it has been widely demonstrated that incomplete block across the ablation lines can be responsible for AT recurrence [228][229][230]. Therefore, if additional linear lesions are applied, line completeness should be demonstrated by mapping or pacing maneuvers.…”
Section: Linear Ablationmentioning
confidence: 93%
“…Linear lesions usually include a roof line connecting the left and right superior PVs and a mitral line connecting the mitral annulus to the left inferior PV (Figure 3) [30, 31, 39, 40]. An anterior line connecting the anterior or anterolateral mitral annulus with the left superior PV has been also proven effective for the treatment of perimitral flutter (Figure 3) [41]. Knecht et al showed that although PVI and electrogram-based ablation without linear lesions are effective for terminating persistent AF in a significant number of patients, macro re-entrant AT requiring LA linear ablation is very likely to occur during the overall follow-up period.…”
Section: Ablation Strategies and Success Rates In Persistent Afmentioning
confidence: 99%
“…Although the efficacy of pulmonary vein isolation (PVI) in paroxysmal AF is well established, PVI alone may not be sufficient in cases with persistent AF (PeAF). In previous studies, additional left atrial (LA) linear lesion formation following PVI has been shown to improve the clinical outcome of RFCA for AF [1][2][3][4][5]. The posterior wall of the LA is known to be one of the non-pulmonary vein (PV) foci and it has been proposed that surgical isolation of posterior wall of the LA combined with all PVs might cure chronic AF with a high success rate [6].…”
Section: Introductionmentioning
confidence: 99%